Structural Analysis in William Shakespeare’s “Bridal Song” - yovita hartarrini (Universitas Aki, 2016)
Mostly, a literary work is a unified whole of art, whereas in art, there are visual and invisible meaning created by its maker. Thus, as a unified whole of art, the meaning of a literary work can be understood through its parts or its composer elements if we can find the reciprocal relationships of the parts so that covering the whole meaning. Any poems, poetry, and prose are fiction works that generally present the world created by the writer through words. The beauty of these works is seen from the entanglement words of language that can be difficult to be comprehended by the reader. As literary study that becomes basic element of research development, structuralism is considered obligatory to be done first. In poetry study using the theory of structuralism, we must pay attention to the elements of poetry because the structuralism study has two main elements in this case are the physical forming as the intrinsic element and the moral message value of any literary works as the extrinsic element. Thus, this research is considered as a kind of flashback study of its composer elements on the classic poetry of Shakespeare. Keywords: literary work, intrinsic element, extrinsic element, structuralism study